2010
DOI: 10.1007/s12665-010-0474-x
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of a sewage sludge application to the short-term carbon sequestration across a wide range of agricultural soils

Abstract: The atmospheric levels of carbon dioxide (CO 2 ) and other greenhouse gases (GHGs) have increased dramatically since the industrial revolution. The atmospheric enrichment with CO 2 and other GHGs has resulted in multiple negative consequences: such as the increase in the average temperature and the rise of the sea level. Hence, there is a growing interest in developing feasible methods to reduce the atmospheric levels of these gases. One of these strategies is to enhance C sequestration through the increase of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 25 publications
2
12
1
Order By: Relevance
“…Here, surface application rates were positively correlated with SOC and total N in the top 15 cm soil layer, somewhat deeper than other studies reporting that SOC and N gains are limited to the top <10 cm of soils [24][25][26][27]. The current results underscore the fact that the effects of application rate and duration on SOC and total N stocks can be highly variable and depend on biosolids-specific composition as well as site-specific factors (e.g., soils, management) [5,7,28].…”
Section: Soil Organic Carbon and Total Nitrogen Stockssupporting
confidence: 54%
“…Here, surface application rates were positively correlated with SOC and total N in the top 15 cm soil layer, somewhat deeper than other studies reporting that SOC and N gains are limited to the top <10 cm of soils [24][25][26][27]. The current results underscore the fact that the effects of application rate and duration on SOC and total N stocks can be highly variable and depend on biosolids-specific composition as well as site-specific factors (e.g., soils, management) [5,7,28].…”
Section: Soil Organic Carbon and Total Nitrogen Stockssupporting
confidence: 54%
“…Agriculture conservation practices such as the use of different cropping and plant-residue management as well as organic management farming can enhance soil carbon storage. Soriano-Disla et al (2010) discussed the contribution of a sewage sludge application to the short-term carbon sequestration across a wide range of agricultural soils. Tian et al (2009) reported that a mean net SCS of 1.73 Mg C ha -1 year -1 derived from a 34-year reclamation using sewage sludge on strip-mined lands.…”
Section: Sustainable Agricultural Practicesmentioning
confidence: 99%
“…Whilst its composition is dependent on wastewater treatment processes, in general terms, is characterized by high levels of organic matter, organic nitrogen, P, Fe and Zn (Fytili & Zabaniotou, 2008). Precisely for these characteristics, when SS is applied as an amendment, it enhances soil fertility and SOM levels, as well as potentially contributes to the short-term carbon sequestration (Soriano-Disla et al, 2010). Consequently, the preferred end use of SS in the EU is found in the agricultural sector, applying to the lands more than 30% of the total production (>10·10 6 t on dry basis) (Mahmoud et al, 2012).…”
Section: Introductionmentioning
confidence: 99%